Investigations on Spin Power Losses Generated in a Planetary Gear Set Using Thermal Network Method - Marie Winger; Yann Marchesse; Thomas Touret; Christophe Changenet; Fabrice Ville; Patrice Gédin (Lubricants)
This paper introduces an experimental approach to study the distribution of power losses in an oil jet-lubricated planetary gear set, with the aim of increasing the efficiency of these gearboxes. A thermal model is developed to estimate power losses associated with temperature distribution. This model is applied to analyze experimental data collected from a dedicated test setup. Different configurations are studied to progressively validate the thermal network. In this paper, only a configuration composed of a rotating ring gear and a fixed planet carrier is studied. This configuration enables the validation of a thermal network developed from a basic configuration where power loss sources are not numerous. The study reveals that, for this configuration, load-independent power losses are primarily attributed to hydrodynamic losses in the bearings, while the gear windage effects are of second order. The power losses are then compared to those generated by the same planetary gear set but using a rotating planet carrier. The comparison shows that the configuration composed of the rotating ring gear and fixed planet carrier produces less power loss than the other configuration.